2021
DOI: 10.11606/s1518-8787.2021055003115
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B prevalence in Brazilian waste pickers: a systematic review with meta-analysis

Abstract: OBJECTIVE: To describe the hepatitis B prevalence in Brazilian waste pickers. METHODS: We performed a literature search in the SciELO, Biblioteca Virtual em Saúde (BVS), PubMed and Web of Science databases using the descriptors: “hepatitis B” AND (“informal recycling” OR “waste picker” OR “recyclable waste collectors” OR “solid waste segregator”) AND (“recyclable waste” OR “solid waste”) AND Brazil. Epidemiological studies on HBV in Brazilian waste pickers published prior to February 2020 were included and eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
0
1
Order By: Relevance
“…The pooled prevalence of HBV infection among waste handlers was 5.07%, with great heterogeneity between its regional states in Ethiopia. The finding of this meta-analysis was lower than the previous findings reported from studies conducted in Nigeria, 36 Brazil, 37 Pakistan, 38 and Central Greece, 39 which showed HBV prevalence rates in waste handlers of 14%, 17.4%, 18.8%, and 23.0%, respectively. The lower prevalence rate of HBV in this study might be explained by differences in the behavioral characteristics of waste handlers recruited in the primary studies.…”
Section: Discussioncontrasting
confidence: 92%
“…The pooled prevalence of HBV infection among waste handlers was 5.07%, with great heterogeneity between its regional states in Ethiopia. The finding of this meta-analysis was lower than the previous findings reported from studies conducted in Nigeria, 36 Brazil, 37 Pakistan, 38 and Central Greece, 39 which showed HBV prevalence rates in waste handlers of 14%, 17.4%, 18.8%, and 23.0%, respectively. The lower prevalence rate of HBV in this study might be explained by differences in the behavioral characteristics of waste handlers recruited in the primary studies.…”
Section: Discussioncontrasting
confidence: 92%